Perturbation of PALB2 function by the T413S mutation found in small cell lung cancer [version 2; referees: 3 approved] - Jean-Yves Bleuyard; Rosie M. Butler; Fumiko Esashi (Wellcome Open Research, 2018)
Background: Germline mutations in the PALB2 gene are associated with the genetic disorder Fanconi anaemia and increased predisposition to cancer. Disease-associated variants are mainly protein-truncating mutations, whereas a few missense substitutions are reported to perturb its interaction with breast cancer susceptibility proteins BRCA1 and BRCA2, which play essential roles in homology-directed repair (HDR). More recently, PALB2 was shown to associate with active genes independently of BRCA1, and through this mechanism, safeguards these regions from DNA replicative stresses. However, it is unknown whether PALB2 tumour suppressor function requires its chromatin association. Methods: Mining the public database of cancer mutations, we identified four potentially deleterious cancer-associated missense mutations within the PALB2 chromatin association motif (ChAM). To assess the impact of these mutations on PALB2 function, we generated cell lines expressing PALB2 variants harbouring corresponding ChAM mutations, and evaluated PALB2 chromatin association properties and the cellular resistance to camptothecin (CPT). Additionally, we examined the accumulation of γH2A.X and the RAD51 recombinase as readouts of DNA damage signalling and HDR, respectively. Results: We demonstrate that a small-cell lung cancer (SCLC)-associated T413S mutation in PALB2 impairs its chromatin association and confers reduced resistance to CPT, the only FDA-approved drug for relapsed SCLC. Unexpectedly, we found a less efficient γH2A.X nuclear foci formation in PALB2 T413S expressing cells, whereas a near-normal level of RAD51 nuclear foci was visible. Conclusions: These findings support the importance of PALB2 chromatin association in the suppression of tumours, including SCLC, an unusually aggressive type of cancer with poor prognosis. PALB2 T413S has little impact on RAD51 recruitment, likely due to its intact interaction with BRCA1 and BRCA2. However, this mutant shows inefficient DNA stress signalling. This finding sheds new light on the function of PALB2, playing a role in efficient DNA stress signalling through constitutive chromatin association.